FORMULA BERBAHAN AKTIF PSEUDOMONAD FLUORESEN DAN PENGARUHNYA TERHADAP PERKEMBANGAN PENYAKIT LAYU PADA CABAI - Yenny Wuryandari; Sri Wiyatiningsih; Maroeto . (Universitas Lampung, 2015)
Formula with active ingridient of fluorescent pseudomonads and its influence on wilt disease development of pepper. The purpose of this study was to synergize organic fertilizer with biopesticides of fluorescent pseudomonads 122 to be the best formula to increase the resistance of pepper plants to wilt disease. The study used a completely randomized design (CRD), which consisted of four treatments. The treatments were forms of active ingredient formula of fluorescent pseudomonads (powder, pellet, granule, and liquid). The effectiveness of the formula in suppressing development of the disease was measured by observing the incubation period, index of the disease and discoloration of vascular tissue of pepper. The results showed that the disease incubation period of plant treated with liquid and powder formula was longer than formula with granule and pellet. Plants treated with powder formula showed the lowest disease index compared to control, liquid, pellet and granule formula. Disease index and discoloration in vascular tissue was also of the lowest value when the plants were treated with powder formula. This result indicate that active ingredient of fluorescent pseudomonads formulated in powder was the most effective to inhibit the development of wilt disease on pepper caused by Fusarium sp. and Ralstonia solanacearum.